#ILoveLondon: An exploration of the declaration of love towards a destination on Instagram. (August 2021) - Filieri, Raffaele; Yen, Dorothy A.; Yu, Qionglei
Abstract: Travellers increasingly use a combination of photographs, texts and hashtags to expressing their attitude towards tourism destinations (TDs). Existing destination branding literature has not yet investigated how consumers express their love towards TDs on social media. This study addresses this knowledge gap and explores how destination brand love (DBL) is expressed on Instagram using a mixed-methods approach. Study one consists of a qualitative visual content analysis of 700 user-generated photographs; while study two adopts text analytics with a sample of 48, 783 posts. The findings show Instagram users' declaration of DBL is expressed through photographs of some destination attributes ( natural & architectural, people, public transportation, food, weather ), accompanied by specific positive emotions ( amazement, attractiveness, pleasure, preference, enchantment, nostalgia, belongingness, intimacy ). The findings also illustrate how Instagram users express their love by providing emotional support when the destination goes through a crisis and that different stakeholders co-create the emotional capital of TDs.